The Criminal Liability for Users of WhatsApp Stickers Containing Pornography - Alif Putra Widiyanto; Abdul Kholiq (Sultan Agung Notary Law Review, 2026)
The development of information and communication technology has not only had a positive impact on society but has also given rise to negative consequences. One of the negative impacts of this technological advancement is the shift in criminal activities from the physical world to the virtual realm. The emergence of cybercrime has driven legal developments to address these new forms of criminal activity. This also applies to the evolution of criminal liability under the criminal law provisions in force in Indonesia. Criminal liability may also be imposed in the context of innovations in information and communication technology, such as in WhatsApp sticker packs containing pornography. In the case of “Batu City Communication and Information Office’s WhatsApp Group Inundated with Pornographic Stickers” and the case of “Female Student Reports to Police After Her Semi-Nude Photo Becomes a WhatsApp Sticker,” the imposition of criminal liability can be seen from the presence of the element of fault under criminal law in accordance with the principle of geen straf zonder schuld (no punishment without fault). In the case of “Batu City Communication and Information Office’s Media WhatsApp Group Inundated with Pornographic Stickers”, criminal liability is centered on the act of using WhatsApp stickers containing pornography, with the victims being members of the Batu City Media Press 2021 WhatsApp group, under the pretext of a joke. The element of fault was established due to the intentional act of sending or using WhatsApp stickers containing pornography in the Batu 2021 Media Press group, as the visual content clearly constituted pornography that violates public decency under criminal law. Meanwhile, in the second case, “Female Student Reports to Police After Her Semi-Nude Photo Becomes a WhatsApp Sticker”, criminal liability is imposed on the perpetrator who created and used the pornographic WhatsApp sticker due to the intentional use of the victim’s photo as a WhatsApp sticker, which violates public decency under criminal law.